AB1001 Online Consultation for Chinese Patients with Rheumatic Diseases Based on Smart System of Disease Management (SSDM) Mobile Tools: A Study of Medical Economics. (15th July 2016) - Xiao, F.; Liu, X.; Wei, H.; Zhou, H.; Wang, H.; Jiang, Y.; Mu, R.; Li, Z.; Jia, Y.; Zhao, Y.; Liu, Y.; Zhang, L.; et al.
Abstract : Background: China has no primary medical care and referral system. Patients can choose any hospitals or any doctors they like to seek medical care in China. As a result, most patients with rheumatic diseases rushed to a few large cities. Survey shows more than 40% of the rheumatic disease patients don't need to go to hospital and they only need advices from specialist. Smart System of Disease Management (SSDM) is a series of applications for chronic diseases management, which develop the interaction between doctors and patients. The study shows that, after training, the RA patients can master the SSDM and perform self-management, including DAS28 and HAQ evaluations, as well as medication and lab test data entries. Objectives: To evaluate the feasibility and benefit of the medical economics of online consultation based on SSDM by rheumatologist. Methods: The rheumatologists implemented the education and training programs on using SSDM and assist the patients in downloading SSDM APP. The SSDM includes doctors' application and patients' application. The patient application includes self-assessment (DAS28, HAQ), medication management, adverse events management and laboratory records. After data entry, patients can synchronize data to the authorized doctor. On the basis of understanding of the disease activities, medication and laboratory test results, the rheumatologists can accept consultation request from their patients, and practice consultation in the form of text or telephone call. Results: Between February 14, 2015 and January 24, 2016, 11 rheumatologists supplied 76 patients with 58 times free and 45 paid consultations. Paid consultations included 34 times text Q&A and 11 telephone consultations. The consulting fee ranged from RMB 50 to 500 yuan (EUR: RMB =1:7.1) each in average of 272.22 ±90.40 yuan, which is approximate to the registration fee in hospital. The total amount of consultation fee was 12, 250 yuan. 87% patients receiving online consultation lived in different city with the rheumatologists. If patients seek medical care in hospital, in addition to the registration fees and medical expenses, the mean cost of transportation, accommodation, meals and lost wages was 1320.39±456.10 (300 - 2, 800) yuan. The total of cost for all patients would have been 160, 450 yuan, which is 13.10 times compared with the cost of online. Through the SSDM system for online consultations, patients can save 92.37% of the cost. Table 1 shows detailed information. Survey shows all patients were satisfied and 64.86% of them were "very satisfied" with the consultations. Conclusions: Using SSDM system to obtain online consultation, Chinese patients with rheumatic disease can enjoy reduced cost with high satisfaction. In the era lack of primary care system in China, SSDM may serve as a complimentary platform to control medical care cost, as well as relieve the tensions between health care professionals and patients. Disclosure of Interest: None declared